CRC handbook of mariculture - McVey, James P. (CRC Press, Inc., 1983)
Topics covered include methods for the culture and preparation of algae, rotifers, Artemia, and other foodstuffs for use in crustacean farms; recent developments on enriching larval food organisms to improve crustacean diets; conditioning and spawning penaeid shrimp; obtaining and manipulating shrimp eggs and sperm for controlled reproduction and use of intensive nursery raceways for juvenile shrimp production; and discussions of many types of marine shrimp growout systems. In addition, culture systems used in Hawaii, Ecuador, Taiwan, and Japan are described in detail. Significant new information from Japan on hormonal control of penaeid shrimp maturation and spawning is discussed. Marine shrimp and Macrobrachium shrimp diseases by the foremost authorities in the area are presented with detailed photographs and illustrations to help identify diseases. The book also includes an update on American lobster larval and juvenile culture.